The Routledge handbook of urban ecology - Douglas, Ian, (Routledge handbooks, 2011)
Introduction / Ian Douglas -- Urban ecology: definitions and goals / N.E. McIntyre -- The analysis of cities as ecosystems / Ian Douglas -- Urban ecology and industrial ecology / Xuemei Bai and Heinz Schandl -- Urban areas in the context of human ecology / Roderick J. Lawrence -- In livable cities in preservation of the wild: the politics of providing for nature in cities / Michael C. Houck -- The human relationship with nature: rights of animals and plants in the urban context / Jason Byrne -- Urban natural histories to urban ecologies: the growth of the study of urban nature / Ian Douglas and David Goode -- Planning for nature in towns and cities: a historical perspective / David Goode -- How much is urban nature worth? And for whom? Thoughts from ecological economics / Anna Chiesura and Joan Martinez-Alier -- Introduction / Ian Douglas -- Climate of cities / C.S.B. Grimmond -- Urban heat islands / T.R. Oke -- Urban effects on precipitation and associated convective processes / J.M. Shephard ... [et al.] -- Urban hydrology / Ian Douglas -- Urban geomorphology / Ian Douglas -- Urban soils / Peter J. Marcotullio -- The process of natural succession in urban areas / Wayne C. Zipperer -- Recombinant ecology of urban areas: characterisation, context and creativity / Colin D. Meurk -- Creative conservation / Grant Luscombe and Richard Scott -- Introduction / Ian Douglas -- Walls and paved surfaces: urban complexes with limited water and nutrients / C. Philip Wheater -- Urban cliffs / Jeremy Lundholm -- Suburban mosaic of houses, roads, gardens and mature trees / Ian Douglas -- Urban wildlife corridors: conduits for movement or linear habitat? / Ian Douglas and Jonathan P. Sadler -- Landscapes parks and open spaces / M. Hermy -- Grassland on reclaimed soil, with streets, car parks and buildings but few or no mature trees / Tony Kendle -- Urban contaminated land / Michael O. Rivett, Jonathan P. Sadler and Bob C. Barnes Urban woodlands as distinctive and threatened nature-in-city patches / C.Y. Jim -- Wetlands in urban environments / Joan G. Ehrenfeld, Monica Palta and Emilie Stander -- Urban animal ecology / Peter J. Jarvis -- Feral animals in the urban environment / Peter J. Jarvis -- Introduction / Ian Douglas -- Intrinsic and aesthetic values of urban nature: a journalist's view from London / David Nicholson-Lord -- Intrinsic and aesthetic values of urban nature: a psychological perspective / Rachel Kaplan -- Urban nature and human physical health / Jenna H. Tilt -- Urban nature: human psychological and community health / Rod Matsuoka and William Sullivan -- Street trees and the urban environment / Gerald F.M. Dawe -- Urban gardens and biodiversity / Kevin J. Gaston and Sian Gaston --Introduction / Ian Douglas -- Urban habitat analysis / Ian Douglas -- Urban habitat type mapping / Peter J. Jarvis -- Invasive species and their response to climate change / Ian Douglas -- Urban biogeochemical flux analysis / Nancy B. Grimm ... [et al.] -- Urban metabolism analysis / Shu-Li Huang and Chun-Lin Lee -- Introduction / Ian Douglas -- Delivering urban greenspace for people and wildlife / John Box -- Urban areas and the biosphere reserve concept / Pete Frost and Glen Hyman -- Urban ecology and sustainable urban drainage / Peter Worrall and Sarah Little -- Green roofs, urban vegetation and urban runoff / Joachim T. Tourbier -- The role of green infrastructure in adapting cities to climate change / Ian Douglas -- Creative use of therapeutic green spaces / Ambra Burls -- Peri-urban ecology: green infrastructure in the twenty-first century metro-space / Joe Ravetz -- Biodiversity as a statutory component of urban planning / David Goode -- Making urban ecology a key element in urban development and planning / John Stuart-Murray.